Instructional Design of Computer Literacy Course with Distance Education - Cabı, Emine (Bartın Üniversitesi, 2021)
In the implementation of the Computer Literacy (CL) course with face-to-face education, there were many problems encountered such as huge number of students who could not reach the education, and the inability to use the physical facilities of the university and the workforce effectively. For the solution of these problems, there was a need for a distance learning environment that is independent of time and space, equipped with rich learning experiences and using new technologies. In this study, it was aimed to prepare an instructional design in order to conduct CL course using distance education technologies and evaluate this design. Accordingly, a course design was prepared to be taught by distance education by following a systematic process according to the analysis, design, development, application and evaluation stages of ADDIE model. The design was evaluated in every process from problem analysis to assessment, especially in the final stage, process and product evaluation were made more comprehensively. Semi-structured interview form and students' academic achievements were used to gather data from the students and instructors. The study is believed to contribute to instructional designers, trainers and experts who want to conduct the course with distance education.

Bilgisayar Okuryazarlığı (BO) dersinin yüz yüze eğitim ile yürütülmesinde öğretimin ulaşamadığı öğrenci sayısının fazla olması, üniversitenin fiziki imkânlarının ve öğretim elemanlarının iş gücünün etkili kullanılamaması problemleri yaşanmıştır. Problemlerin çözümü için, zaman ve mekândan bağımsız, zengin öğrenme yaşantılarıyla donatılmış ve yeni teknolojilerin kullanıldığı uzaktan öğrenme ortamına ihtiyaç duyulmuştur. Bu çalışmada, BO dersinin uzaktan eğitim teknolojileri kullanılarak yürütülmesi için öğretim tasarımı hazırlamak ve tasarımı değerlendirmek hedeflenmektedir. Bu doğrultuda analiz, tasarım, geliştirme, uygulama ve değerlendirme aşamaları ile ADDIE modeline göre sistematik bir süreç izlenerek uzaktan öğretim ile verilecek bir ders tasarımı hazırlanmıştır. Problem analizinden değerlendirme aşamasına kadar her süreçte tasarım değerlendirilmiş, özellikle son aşama olan değerlendirme aşamasında süreç ve ürün değerlendirme daha geniş kapsamlı yapılmıştır. Öğrenci ve eğitmelerden yarı yapılandırılmış görüşme formu, öğrencilerin akademik başarıları ile veriler elde edilmiştir. Çalışma uzaktan eğitim ile dersi yürütmek isteyen öğretim tasarımcılarına, eğitmenlere ve uzmanlara katkı sağlayacağı düşünülmektedir.
Uzaktan Eğitim ile Bilgisayar Okuryazarlığı Dersinin Öğretim Tasarımı
Keywords: Other Fields of Education; Alan Eğitimleri